2023
DOI: 10.3390/pharmaceutics15061591
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers in Corneal Drug Delivery: Recent Developments and Translational Opportunities

Anubhav Dhull,
Carson Yu,
Alex Hunter Wilmoth
et al.

Abstract: Dendrimers are biocompatible organic nanomaterials with unique physicochemical properties, making them the focus of recent research in drug delivery. The cornea of the human eye presents a challenge for drug transit due to its inherently impenetrable nature, requiring nanocarrier-mediated targeted drug delivery. This review intends to examine recent advancements in the use of dendrimers for corneal drug delivery, including their properties and their potential for treating various ocular diseases. The review wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…IL-13 is expressed in neurons and can modulate neuronal activity and synaptic plasticity 73 . Studies have shown that IL-13 protects neurons against excitotoxic insults after TBI 22 . There were significant differences in the IL-13 expression based on treatment [F (3, 30) =15.41, p < 0.0001].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-13 is expressed in neurons and can modulate neuronal activity and synaptic plasticity 73 . Studies have shown that IL-13 protects neurons against excitotoxic insults after TBI 22 . There were significant differences in the IL-13 expression based on treatment [F (3, 30) =15.41, p < 0.0001].…”
Section: Resultsmentioning
confidence: 99%
“…Within the realm of polymer-based nanoparticulate drug delivery systems, dendrimers, which are hyper-branched, uniformly sized, monodispersed synthetic macromolecules with precisely defined structure and composition, have gained extensive utilization in the field of drug delivery systems 21 , 22 . This arises from the meticulous control over their properties like molecular structure, size, shape and solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers are nanoscale macromolecules characterized by a tree-like or dendritic structure, featuring highly branched repeating units radiating from a central core. The three-dimensional shape and size of the dendrimer are determined by the number and arrangement of arms comprising its core, while its physiochemical proprieties are dictated by the surface groups [ 99 ].…”
Section: Nano-based Drug Delivery Systems In Dry Eye Diseasementioning
confidence: 99%
“…It can also significantly prolong the half-life of the drug in the body and minimize the frequency of drug administration. In addition, the surface of dendrimers is densely covered with various functional groups, which can specifically bind to target cells after modification, realizing the targeted delivery of DOX and enhancing the chemotherapeutic effect of TNBC ( Mukherjee et al, 2022 ; Dhull et al, 2023 ). Thus, based on these properties of dendrimers, they have led to the development of novel drug delivery technologies.…”
Section: Novel Nano-drug Delivery Systemsmentioning
confidence: 99%